A New Species of the Aplastodiscus albosignatus Group (Hylinae: Cophomantini) from the Northern Mantiqueira Mountain Range - Marinho, Pedro [UNESP]; Santos, Marcus Thadeu T. [UNESP]; Faivovich, Julian; Lyra, Mariana L. [UNESP]; Giaretta, Ariovaldo A.; Haddad, Célio F.B. [UNESP]; Carvalho, Thiago R. [UNESP] (Herpetologists League, 2024)
The genus Aplastodiscus (Hylidae) is widely distributed in the Atlantic Forest of Brazil and adjacent Argentina, and a single species inhabits the Cerrado in Central Brazil. The genus comprises 16 species included in 4 species groups. The A. albosignatus species group contains 6 described species, as well as two candidate species referred to as Aplastodiscus sp. 5 and Aplastodiscus sp. 6 in previous studies. Here we name and describe Aplastodiscus sp. 6, based on morphology, DNA sequences, and vocalizations. The new species is known only from the northern sector of the Mantiqueira Mountain Range and can be distinguished morphologically from most congeneric species based on body size, iris color pattern, and cloacal ornamentation. The new species is distinguished from its sister species A. leucopygius by its vocalization. The species of the A. albosignatus group share a conserved external morphology and most of the morphological characters traditionally included in their diagnoses failed to distinguish them. In contrast, advertisement call traits, such as call duration, call envelope, and distribution of sound energy in the harmonic series, were informative in Aplastodiscus species discrimination.
Keywords: Anura; Hylidae; Phylogeny; Taxonomy; Tree Frogs; Vocalizations